Dear Thing - Cohen, Julie, 1970- (London Bantam, 2013)
Claire and Ben are the perfect couple. But behind the glossy fa ade, they've been desperately trying u and failing u to have a baby for years. Now, the stress and feelings of loss are taking their toll on their marriage. Claire's ready to give up hope and get on with her life, but Ben is not. And then Ben's best friend, Romily, offers to conceive via artificial insemination and carry the baby for them. Romily acts in good faith, believing it will be easy to be a surrogate. She's already a single mother, and has no desire for any more children. Except that being pregnant with Ben's child stirs up all sorts of emotions in her, including one she's kept hidden for a very long time: Ben's the only man she's ever loved. Two mothers and one baby who belongs to both of them, and which only one of them can keep.
Keywords: Friendship -- Mothers -- Pregnancy